Detection and root cause analysis of minor tread defects in tire manufacturing using optical laser profilometry and fault tree analysis - Arwan Suwandoyo; Daisman Purnomo Bayyu Aji (Jurnal Polimesin, 2026)
Tire tread quality plays an important role in tire performance, safety, and service life. Minor tread defects, characterized by local surface irregularities and thickness deviations, remain a common challenge in tire manufacturing due to their impact on dimensional consistency. This study presents a method for detecting minor thread defects using a non-contact optical laser profilometer, with a measurement accuracy of 0.1 mm, to obtain high-resolution tread surface profile mapping. The purpose of this study is to address the issue of minor tread defects by integrating a non-contact optical laser profilometer with Fault Tree Analysis (FTA). After improvements to the method, the results show that the average percentage of defects can be reduced from an average of 0.07% to an average of 0.03%. The factor causing severe tread defects is the material with a small volume in the tread thickness. In tread measurement, laser triangulation technology generates contour data without physical contact, preventing deformation and enabling measurements of elastic materials. The scanned data were processed using a contour-extraction algorithm and geometric deviation analysis to identify anomalies, such as variations in tire tread depth. Experimental results showed a thickness deviation of −0.69 mm at a width of 15 mm, exceeding the permissible tolerance limit of +0.3 mm, indicating a condition significantly outside the specifications or standards for the tire tread material. The measurement system demonstrated high repeatability and sensitivity in detecting local surface deviations that could not be identified through visual inspection. Furthermore, integrating the optical laser profilometer with FTA enabled the systematic identification of the root cause of the defect, traced to a dimensional mismatch in the tire tread extrusion die. The implementation results could reduce or decrease light tread defects and the total percentage of light tread defects in tires.